Silver-coated gold nanorods as a promising antimicrobial agent in the treatment of cancer-related infections - Zhang J (Dove Medical Press, 2018)
Junyan Zhang,1 Mian Wang,1 Thomas J Webster1,2 1Department of Chemical Engineering, Northeastern University, Boston, MA, USA; 2Wenzhou Institute of Biomaterials and Engineering, Wenzhou Medical University, Wenzhou, Zhejiang, China Background: Many cancer patients suffer from cancer-related life-threatening infections due to immune system damage. Therefore, researchers are continuously looking for new options to treat cancer-related infections. As nanotechnology has gained tremendous interest over the past several decades, silver nanoparticles have been investigated as an effective antimicrobial agent. Here, silver-coated gold nanorods were synthesized to share similar optical properties as gold nanoparticles for cancer diagnosis and treatment, with an added advantage of antibacterial properties. Results: Their dose-dependent antimicrobial properties were demonstrated on both Gram-negative and Gram-positive bacteria species. These nanorods were found to be highly efficient in killing bacteria and suppressing biofilm formation. Conclusion: Collectively, such results suggest that silver-coated gold nanorods should be further investigated as a novel material, which can both decrease cancer cell functions and reduce the risk of infection for cancer patients. Keywords: nanotechnology, bacteria, cancer cells, infrared excitation